Enzymes in drug metabolism (Henry Stewart Talks, 2026)
Role of enzymes in drug metabolism, Phases of drug metabolism, Cytochrome P450 enzyme functions, Conjugating enzymes in Phase Two, Influences on enzyme activity, Enzyme induction and inhibition, Pharmacogenomics in personalized medicine